EFFECTIVENESS OF PRINCIPAL COMPETENCY MANAGEMENT MODEL BASED ON LESSON STUDY IN IMPROVING THE QUALITY OF ACADEMIC SUPERVISION AND LEARNING IN STATE HIGH SCHOOLS - M. Basir. S. Hasibuan; Syawal Gultom; Wildansyah Lubis (RADJA PUBLIKA, 2025)
This study aims to examine the effectiveness of a Lesson Study-Based Principal Competency Management Model in improving the quality of academic supervision and learning in public senior high schools (SMA Negeri) in Langkat Regency. Using a Research and Development (R&D) approach, the model was designed through a series of stages: preliminary study, model development, limited trials, extended trials, and final implementation. The model integrates the core principles of Lesson Study (Plan–Do–See–Act) into the principal's role as an instructional leader. The results showed that the model is valid, practical, and effective. Principals who implemented the model demonstrated increased competence in academic supervision, engaged in reflective discussions with teachers, and supported the improvement of teaching practices. The Lesson Study cycle empowered principals not only as administrators but also as facilitators of professional learning. The model also fostered a collaborative culture among educators and had a positive impact on the quality of classroom instruction. Based on these findings, the model is recommended for broader implementation and policy integration in professional development programs for school leaders.